2010
DOI: 10.15560/6.2.301
|View full text |Cite
|
Sign up to set email alerts
|

Holocene molluscs from Rio de Janeiro state coast, Brazil

Abstract: A list of marine species of bivalves and gastropods found in seventy archeological sites of the shellmound type from Rio de Janeiro state was produced, based on the archeological material deposited in the collections of Museu Nacional (Rio de Janeiro, RJ), Instituto de Arqueologia Brasileira (Belford Roxo, RJ) and Museu do Sambaqui da Tarioba (Rio das Ostras, RJ). A total of 124 taxa were identified, of which 65 bivalves and 59 gastropods. The data retrieved from the shellmounds indicate stability of the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 4 publications
(4 reference statements)
1
15
0
8
Order By: Relevance
“…The shell mounds along the coastal lagoon region of the Rio de Janeiro state (e.g., Tarioba, Manitiba, Beirada and Ponte do Girau) range in age between 5100 and 1300 cal BP (Kneip, 2001;Angulo et al, 2007;Ten orio et al, 2010;Macario et al, 2014) and are primarily composed of shell of edible marine mollusks, fish remains and wildlife bones intermixed with sand and remains of precolonial civilization (Dias, 2001;Kneip, 2001;Ten orio et al, 2010). Previous studies of the faunal remains found in these sites (Kneip, 2001;Souza et al, 2010) revealed that the primary fish target by the precolonial communities was the whitemouth croaker (Sciaenidae, Micropogonias furnieri). Radiocarbon isotope age dating from material of these shell mounds used mollusks (calcite), otoliths (aragonite) and charcoal, and have resulted in an accurate age and reservoir data (Macario et al, , 2015Carvalho et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…The shell mounds along the coastal lagoon region of the Rio de Janeiro state (e.g., Tarioba, Manitiba, Beirada and Ponte do Girau) range in age between 5100 and 1300 cal BP (Kneip, 2001;Angulo et al, 2007;Ten orio et al, 2010;Macario et al, 2014) and are primarily composed of shell of edible marine mollusks, fish remains and wildlife bones intermixed with sand and remains of precolonial civilization (Dias, 2001;Kneip, 2001;Ten orio et al, 2010). Previous studies of the faunal remains found in these sites (Kneip, 2001;Souza et al, 2010) revealed that the primary fish target by the precolonial communities was the whitemouth croaker (Sciaenidae, Micropogonias furnieri). Radiocarbon isotope age dating from material of these shell mounds used mollusks (calcite), otoliths (aragonite) and charcoal, and have resulted in an accurate age and reservoir data (Macario et al, , 2015Carvalho et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, by-catch occurred; that is, species with no known anthropological relevance were incidentally fished with target species (Reitz & Wing 2008, Villagran & Gianini 2014, Beuclair et al 2016. Therefore, midden records are a good indicator of Holocene biodiversity, providing data on fish species composition, abundance, distribution and richness as well as cultural information (diet, fishing gear, ritualistic symbols, ornaments and artefacts) (Souza et al 2010a, Souza et al 2010b, Faria et al 2014, Mendes et al 2014, Rodrigues et al 2016a, Rodrigues et al 2016b, Beuclair et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Os vestígios zooarqueológicos têm sido usados, quase que exclusivamente, para interpretação de hábitos alimentares, economia doméstica e aspectos culturais. Mais recentemente, os vestígios zooarqueológicos de sambaquis começaram a ser utilizados para inferências sobre a constituição da fauna do Holoceno Recente [14,15,16,17,18,19].…”
Section: Introductionunclassified
“…Bem como, a partir de levantamento bibliográfico, produzir fichas informativas referente às espécies tombadas. Esta coleção tem servido como referência para estudos taxonômicos [14,19], biológicos [26], arqueológicos [15], de evolução da biodiversidade [16,17], datações por radiocarbono [27,28] e paleoambientes [29]. Além disso, tem atendido a projetos de educação ambiental junto a escolas públicas [30].…”
Section: Introductionunclassified